Identification of Cardiomyocyte-Fated Progenitors from Human-Induced Pluripotent Stem Cells Marked with CD82 - Takeda, Masafumi; Kanki, Yasuharu; Masumoto, Hidetoshi; Funakoshi, Shunsuke; Hatani, Takeshi; Fukushima, Hiroyuki; Izumi-Taguchi, Akashi; Matsui, Yusuke; Shimamura, Teppei; Yoshida, Yoshinori; Yamashita, Jun K. (Cell reports (Cambridge), 2018)
Here, we find that human-induced pluripotent stem cell (hiPSC)-derived cardiomyocyte (CM)-fated progenitors (CFPs) that express a tetraspanin family glycoprotein, CD82, almost exclusively differentiate into CMs both in vitro and in vivo. CD82 is transiently expressed in late-stage mesoderm cells during hiPSC differentiation. Purified CD82+ cells gave rise to CMs under nonspecific in vitro culture conditions with serum, as well as in vivo after transplantation to the subrenal space or injured hearts in mice, indicating that CD82 successfully marks CFPs. CD82 overexpression in mesoderm cells as well as in undifferentiated hiPSCs increased the secretion of exosomes containing β-catenin and reduced nuclear β-catenin protein, suggesting that CD82 is involved in fated restriction to CMs through Wnt signaling inhibition. This study may contribute to the understanding of CM differentiation mechanisms and to cardiac regeneration strategies. [Display omitted] •Cardiomyocyte (CM)-fated progenitors (CFPs) from human iPSCs•CD82 as a specific cell-surface CFP marker•Specific differentiation of CD82+ cells to CMs in vitro and in vivo•CD82 in CM-fate restriction through exosome-mediated Wnt inhibition Takeda et al. find that CD82+ is a cell-surface marker on cardiomyocyte-fated progenitors made from human iPSCs.